If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -2(-6x + -1) = -1 Reorder the terms: -7 + -2(-1 + -6x) = -1 -7 + (-1 * -2 + -6x * -2) = -1 -7 + (2 + 12x) = -1 Combine like terms: -7 + 2 = -5 -5 + 12x = -1 Solving -5 + 12x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 12x = -1 + 5 Combine like terms: -5 + 5 = 0 0 + 12x = -1 + 5 12x = -1 + 5 Combine like terms: -1 + 5 = 4 12x = 4 Divide each side by '12'. x = 0.3333333333 Simplifying x = 0.3333333333
| h(t)=t^3+2t^2-3t+1 | | y-4/x=2/5 | | -4=w-6 | | 2(-3x-4)=-15 | | -x-10+3x+15=-2 | | 1856=-210(-9)+b | | 27a+95=0 | | 1226=-210(-6)+b | | 27=3*y | | 8-5n=-32 | | 0.25x^2-2x+10=0 | | 32=9a-4-3a | | cos(60)=x/7 | | (2x)*(x^2/3) | | -6+u=9 | | x^3-10y+25=0 | | 2x*x^2/3 | | 12=3u-12 | | y^3-10y+25=0 | | 2x^2+2x-612=0 | | 8x-14-6x-13=-6 | | 4*u=20 | | 0.4y/0.4 | | 2u+12=34 | | 12=3*w | | x+x+3+x+7= | | x+(x+3)+(x+7)= | | -2(5-4x)=6x-4 | | 4x-12=16+8x | | 2x-x-2x^2=-15 | | f(3)+f(-3)=5x-3 | | 4*3x-3x+1=81 |